« Devenir inverseur ». Trajectoire de participation d’une enseignante à un tweetchat animé par le collectif Inversons la classe ! - Sylvie Mas (Recherches en Éducation)
The practice known as the "flipped classroom" was developed around 2006. Less than ten years later, this practice is enjoying a certain craze. This craze is shown in France by the creation in 2014 of the collective Inversons la classe! which is devoted to training in the practices of the flipped classroom approach. The phenomenon of online communities and the interest of research for professional development in these spaces is not new. However, it is renewed with the rise of the social web and its uses by teachers and teachers' collectives. Many studies question the interest of professional interactions on digital social networks for professional development. Our data consist of activity traces from digital social networks and an interview. They allow us to describe an individual trajectory of participation in relation to the selected professional development indicators. Our results indicate that reported changes in practice were not socially constructed during discussions with other participants. They rather reveal a progressive engagement in a process of identity negotiation. Therefore, the teacher gradually finds the recognition of the collective, thanks of the relationship built with a main figure of the Network.